Ritual Adat Antar Padi: Konstruksi Teologi Kontekstual - Eva Salomin Kulapupin (Program Pascasarjana UKIM, 2021)
From the many existing customs, one is very good and shows the sibling relationship between the immigrant community and the indigenous people of Aru. The Aru Islands have long been a place of trade because they have great natural products. Therefore, many immigrants of the Aru island to trade. It creates a sibling relationship between the two tribes. The association is framed in the Jabu-jabu bond. This Jabu relationship is established between 6 villages in the Aru Islands and one of the immigrant tribes. This bond occurs because there is a history, so they always perform traditional rituals every few years. This bond occurs when the Koba gets the Bugis and asks for rice. The Bugis people told them about the place, and during the process of taking their rice, they were helped by people from 3 villages in the Aru Islands. In the city of Dobo the immigrants (BBM and China) are more economically developed than the natives. Therefore, there is a need for a genuine understanding of how indigenous Aru people and immigrants should coexist reasonably and grow together. This research concludes that the immigrant community must respect the indigenous population and vice versa to advance the Aru Islands area. In addition to maintaining relationships with others, awareness to protect the environment is also very important. As the people of Koba and Jabu-Jabu see rice as a source of life, it must be manifested in all the universes. In this way, God can be understood as the source of universal brotherhood. And the Aru people embody it in their daily lives.